2017
DOI: 10.1177/1362361316676204
|View full text |Cite
|
Sign up to set email alerts
|

Joint attention difficulties in autistic adults: An interactive eye-tracking study

Abstract: Joint attention - the ability to coordinate attention with a social partner - is critical for social communication, learning and the regulation of interpersonal relationships. Infants and young children with autism demonstrate impairments in both initiating and responding to joint attention bids in naturalistic settings. However, little is known about joint attention abilities in adults with autism. Here, we tested 17 autistic adults and 17 age- and nonverbal intelligence quotient-matched controls using an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 49 publications
7
43
1
2
Order By: Relevance
“…A study's sample size is halved given that all participants are studied in pairs and the unit of analysis is the dyad rather than the individual. While the sample size in the current study may seem small, it is comparable to or even higher than other sample sizes in both autism research [107,108] and IPS research [34,71,[109][110][111]. Nevertheless, it is important to note that, in order to compare between groups with sufficient power and to investigate associations with other variables more extensively, the present results would need to be replicated with a larger sample.…”
Section: Sample Limitationsmentioning
confidence: 67%
“…A study's sample size is halved given that all participants are studied in pairs and the unit of analysis is the dyad rather than the individual. While the sample size in the current study may seem small, it is comparable to or even higher than other sample sizes in both autism research [107,108] and IPS research [34,71,[109][110][111]. Nevertheless, it is important to note that, in order to compare between groups with sufficient power and to investigate associations with other variables more extensively, the present results would need to be replicated with a larger sample.…”
Section: Sample Limitationsmentioning
confidence: 67%
“…Empirical evidence for atypical gaze behavior and atypical processing of gaze cues in individuals with ASD is now overwhelming, in particular early aversion of social gaze (Jones and Klin, 2013), altered attention preferences for social cues in form of gaze avoidance (Madipakkam et al, 2017) and less contact or involvement evoked by direct gaze (Schwartz et al, 2010). Gaze idiosyncrasies were already found in children with ASD (Jones and Klin, 2013) and are still present in adults (Schwartz et al, 2010;Georgescu et al, 2013;Madipakkam et al, 2017;Caruana et al, 2018) and are not caused by oculomotor disfunctions (Caruana et al, 2018). In conclusion, empirical evidence from several domains indicate reduced body motion alignment, less anticipation of other persons' kinematics in motor planning as well as atypical social gaze as features of individuals with ASD that contribute to INTERpersonal dissynchrony (see Table 1 for an overview).…”
Section: Interpersonal Dissynchronymentioning
confidence: 99%
“…The results observed in the Human group replicated the findings of our previous studies in which all participants have believed their virtual partner to be human-controlled (Caruana et al 2015;Caruana, Stieglitz Ham et al, 2017;Caruana et al, 2017b). In the Respond conditions, participants responded more slowly to the eye gaze cue during the Social condition (RJA) than the arrow cue in Control condition (RJAc).…”
Section: Discussionsupporting
confidence: 86%
“…They also made more premature attempts at initiating joint attention before their virtual partner had returned his gaze to establish eye contact (cf. Caruana et al 2015;Caruana, Stieglitz Ham et al, 2017;Caruana et al, 2017b). As predicted, we found that both effects were reduced in the Computer group.…”
supporting
confidence: 89%
See 1 more Smart Citation